2022
DOI: 10.1080/1034912x.2022.2092078
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Disability and Burnout among Teachers in Inclusive Schools in France

Abstract: Western countries have placed a lot of importance on school inclusion policies in the last decade. Strong promotion of these policies encourages teachers to express egalitarian attitudes and behaviours towards all students. However, at the same time teachers may experience feelings of discomfort because of perceived difficulties and powerlessness in implementing the inclusion policy. The discrepancy between what teachers say and their internal discomfort can lead to burnout. The aim of this study was to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(87 reference statements)
1
2
0
Order By: Relevance
“…The difference in early empathic reactions between the two groups can be connected to findings suggesting that the affective component of empathy is a hallmark of prejudice (for a synthesis, see Han, 2018). This is consistent with many of the findings regarding attitudes towards people with disabilities indicating a gap between benevolent intentions and prejudice (Rohmer, Palomares et al, 2022).…”
Section: Discussionsupporting
confidence: 77%
“…The difference in early empathic reactions between the two groups can be connected to findings suggesting that the affective component of empathy is a hallmark of prejudice (for a synthesis, see Han, 2018). This is consistent with many of the findings regarding attitudes towards people with disabilities indicating a gap between benevolent intentions and prejudice (Rohmer, Palomares et al, 2022).…”
Section: Discussionsupporting
confidence: 77%
“…Many feel the need to function as if nothing has happened, even though this may be at the expense of their own health and psychological well-being [26,27] . Rohmer et al [28] or Marič et. al.…”
Section: Causes Of Burnout In Teachersmentioning
confidence: 99%
“…For example, to what extent is the contribution of lay beliefs about factors that make a child successful or not at school taken into account when inclusion fails? The involvement of teachers' attitudes and beliefs in the success of inclusion has recently been analyzed through social psychology lenses (Bastart, Rohmer, & Popa‐Roch, 2021; Jury et al, 2021; Rohmer, Palomares, & Popa‐Roch, in press; Vaz et al, 2015). A few studies revealed that teachers' beliefs predict students' academic outcomes (Hornstra, Dedessen, Bakker, Van den Bergh, & Voeten, 2010; Van den Bergh, Denessen, Hornstra, Voeten, & Holland, 2010).…”
Section: Introductionmentioning
confidence: 99%